Influence of Celebrity Appeal and Halal Label on Wardah Purchase Decisions: Role of Brand Image - Achmad Agus Priyono; Ahmat Nurulloh (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study aims to analyze the influence of celebrity endorsements and halal labels on purchasing decisions for Wardah cosmetic products, with brand image as a mediating variable. This study used a quantitative explanatory approach involving 65 student respondents from private universities in Malang City. Data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The results showed that celebrity endorsements and halal labels significantly influenced brand image, but did not have a direct or indirect influence on purchasing decisions. This finding reflects a shift in the behavior of Generation Z Muslim consumers from a symbolic orientation to a functional evaluation in assessing halal products. Although brand image is formed positively through celebrity endorsements and halal labels, this is not enough to directly drive purchase intentions, so a more authentic and experience-based marketing approach is needed. Theoretically, this study contributes by expanding the consumer behavior model through consideration of brand trust and digital engagement as additional constructs. The practical implication is that brands like Wardah need to prioritize branding strategies that are more immersive, transparent, and focused on creating shared value to address the increasingly complex and digitally connected dynamics of the modern halal market.